BOTULINUM TOXIN TYPE A IN NEUROLOGY: CURRENT INDICATIONS, EFFICACY, AND SAFETY - Szwed, Agnieszka; Warzocha-Żurek, Daria Aleksandra; Borzęcka, Katarzyna Anna; Ziemba-Furgała, Natalia Matylda; Polewczak-Karp, Ewa Maria; Andryszko, Krystian; Wawrzonek, Katarzyna; Sołtys, Aleksandra; Dymon, Marcelina; Krysa, Paulina (International Journal of Innovative Technologies in Social Science, 2026)
Background: Botulinum toxin (BoNT), a neurotoxin produced by Clostridium botulinum, has become an established therapeutic modality in neurology. Its mechanism of action—based on the inhibition of acetylcholine release through cleavage of SNARE proteins—results in reversible chemodenervation of hyperactive muscles. Beyond its neuromuscular effects, BoNT modulates sensory neurotransmission, including inhibition of calcitonin gene-related peptide (CGRP) release, which underlies its role in pain disorders. Over the past decades, its clinical indications have expanded, particularly in dystonia, spasticity, and chronic migraine.Methods: A semi-systematic review of the literature was conducted using major medical databases, including PubMed, Scopus, and Google Scholar. The search included studies published between 2000 and 2025, with emphasis on randomized controlled trials, meta-analyses, and international guidelines. Key clinical trials, including the PREEMPT program and pivotal studies in dystonia and post-stroke spasticity, were analyzed with focus on clinical efficacy, safety, and applicability.Results: High-level evidence supports the use of botulinum toxin type A as first-line therapy for cervical dystonia and blepharospasm (Level A recommendation). In post-stroke upper limb spasticity, BoNT-A significantly reduces muscle tone as measured by validated scales, with consistent evidence from RCTs and meta-analyses supporting its efficacy (Level A). Functional improvement is variable and depends on individualized goal setting and integration with rehabilitation. In chronic migraine, the PREEMPT trials demonstrated a significant reduction in monthly headache days and improved quality of life, establishing BoNT-A as an evidence-based preventive therapy for patients with ≥15 headache days per month. The safety profile across indications is favorable, with predominantly mild and transient adverse events.Conclusions: Botulinum toxin represents a cornerstone of focal therapy in several neurological disorders. The strongest evidence supports its use in dystonia, focal spasticity, and chronic migraine. Appropriate patient selection, precise injection technique, and integration into comprehensive management strategies are critical for optimal outcomes. Ongoing research aims to refine patient stratification and clarify its role alongside emerging biologic therapies.